PELATIHAN STUDI KELAYAKAN BISNIS: PENINGKATAN KUALITAS DAN DAYA SAING USAHA PADA UMKM MELALUI PENDEKATAN BMC - Inanda Shinta Anugrahani; Ferby Mutia Edwy (Gapenas Publisher, 2023)
Business feasibility studies have an important role in the success of business actors in carrying out their business activities. The insights of this business feasibility study are expected to provide a change in the concept of thinking of entrepreneurs in achieving measurable success. The purpose of this community service is to provide insight for business actors regarding business feasibility studies to improve the quality and competitiveness of SMEs through BMC. Business planning and business feasibility tests through the BMC approach are considered very easy and complete so that they can accommodate a business plan with nine elements in the BMC dialog box. This community service activity was carried out on October 29, 2022 in Malang City with 25 participants. The result of service activities is that MSMEs managed by young entrepreneurs can understand the importance of business feasibility studies and apply business with a BMC approach. This community service activity does not only take place offline, but is continued with assistance to business actors in order to improve the quality and competitiveness of businesses so as to be able to build the economic welfare of the Indonesian people